2019
DOI: 10.1113/ep087332
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue remodelling induced by corticosterone in male Wistar rats

Abstract: New Findings What is the central question of this study?Does glucocorticoid excess disrupt brown adipose tissue (BAT) phenotype and function? What is the main finding and its importance?Glucocorticoid excess induced an extensive remodelling of interscapular BAT, resulting in a white‐like phenotype in association with metabolic disturbances. Glucocorticoids might be an important modulator of BAT physiology and BAT may have a role in pathophysiology of metabolic disturbances induced by glucocorticoid excess. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 61 publications
3
16
0
Order By: Relevance
“…Studies from our laboratory showed that corticosterone treatment resulted in lipid accumulation and a decrease in basal and norepinephrine-induced UCP1 mRNA and protein content in BAT of both male and female mice (36,146,147). These effects were confirmed by others in a study in which male rats were treated with corticosterone for 21 days (148). In in vitro differentiated brown adipocytes, GCs reduced the norepinephrine-stimulated Ucp1 mRNA expression (147,149).…”
Section: Effects Of Glucocorticoids On Batsupporting
confidence: 63%
“…Studies from our laboratory showed that corticosterone treatment resulted in lipid accumulation and a decrease in basal and norepinephrine-induced UCP1 mRNA and protein content in BAT of both male and female mice (36,146,147). These effects were confirmed by others in a study in which male rats were treated with corticosterone for 21 days (148). In in vitro differentiated brown adipocytes, GCs reduced the norepinephrine-stimulated Ucp1 mRNA expression (147,149).…”
Section: Effects Of Glucocorticoids On Batsupporting
confidence: 63%
“…Lipid accumulation in BAT upon GC treatment has been reported previously (Ketzer et al, 2019;Luijten et al, 2019;Shen et al, 2017;Strack et al, 1995), but here we show for the first time that flattening of daily corticosterone oscillations in mice leads to lipid accumulation in BAT as well. We hypothesized that this could impact the functionality of the tissue.…”
Section: Discussionsupporting
confidence: 81%
“…With the discovery of thermogenic brown adipocytes in humans (Cypess et al, 2009;Saito et al, 2009;Van Marken Lichtenbelt et al, 2009), BAT expansion or boosting its respiratory activity has gained significant attention as a therapeutic treatment for obesity and related disorders (Betz and Enerbäck, 2015;Harms and Seale, 2013;Kusminski et al, 2016;Sidossis and Kajimura, 2015). Numerous studies showed that GC treatment in rodents can lead to accumulation of lipids in the brown fat depot (Ketzer et al, 2019;Luijten et al, 2019;Shen et al, 2017;Strack et al, 1995).…”
Section: Flattening Of Daily Corticosterone Oscillations In Mice Resumentioning
confidence: 99%
“…A study performed in male rats showed that the addition of CORT (0.1-0.5 mg/mL) to drinking water for 21 days induced the remodelling of BAT to WAT, resulting in an increase in whole-body adiposity. Representative BAT samples from these rats documented a reduction in UCP1 mRNA and protein expression along with an increase in WAT-specific gene expression, such as fatty acid synthase, as responsible for lipid accumulation [89]. A study of diet-induced obese mice subjected to a seven week treatment of DEX (5 mg/kg) injection every other day showed a decrease in BAT ucp1 mRNA expression and increased body fat percentage [92].…”
Section: Effects Of Gcs On Bat Lipid Metabolismmentioning
confidence: 98%
“…An increase in BAT thermogenic activity is one suggested therapeutic method to decrease AT lipid accumulation and prevent the development of obesity and other metabolic diseases [39]. GCs reduce the BAT-specific thermogenic and metabolic characteristics and induce whitening in BAT [89,90]. GCs also increase lipid accumulation in BAT, while decreasing non-shivering thermogenesis [40].…”
Section: Effects Of Gcs On Bat Lipid Metabolismmentioning
confidence: 99%